A feasible process for lead-free Cs2SnI6 films using vapor-assisted deposition method with Sn and I2 powders as reactants. (25th January 2021) - Wang, Jiaming; Ullah, Saad; Yang, Peixin; Liu, Linlin; Yang, Shi-E; Xia, Tianyu; Guo, Haizhong; Chen, Yongsheng
Abstract: As potential candidates for organic–inorganic hybrid perovskite materials, Pb-free Cs2 SnI6 has gained considerable attention because of their better stability under atmospheric conditions containing oxygen and water vapor. Herein, we fabricate Cs2 SnI6 films using the vapor-assisted deposition method with Sn and I2 powders as reactants. To obtain uniform and pure Cs2 SnI6 films, two different reaction systems are applied and the properties of the samples are characterized via x-ray diffraction, scanning electron microscopy, UV–vis spectrometer, photoluminescence, and Hall-effect measurements. All the results showed a strong dependency on the reaction temperature and fabrication approach. Based on the preparation process in a closed system, we successfully inhibited the high temperature decomposition of Cs2 SnI6 even at 250 °C. However, in the open system, the reaction temperature of Cs2 SnI6 films should not be higher than 200 °C. Finally, n-type semiconducting Cs2 SnI6 films with bandgap ( E g ) of 1.32–1.54 eV, carrier concentration of 10 13 –10 16 cm −3, and carrier mobility above 100 cm 2 V −1 s −1 are obtained due to the generated I-rich synthesis condition. We believe that our findings will provide beneficial guidance for the fabrication of Cs2 SnI6 perovskite solar cells.